Shape Measurement of a Sewer Pipe Using a Mobile Robot with Computer Vision. (18th January 2013) - Kawasue, Kikuhito; Komatsu, Takayuki
A mobile robot equipped with two lasers and a CCD camera for pipe inspection is proposed. Circular laser streaks that appeared on the inner surface of the pipe reveal the shape of the pipe. The 3D shape of a sewer pipe can be reconstructed considering the movement of the mobile robot along the pipe. Since the tilt of the mobile robot with respect to the axis of the pipe appears as the deformation between two circular streaks, the shape of a sewer pipe can be measured accurately, regardless of the tilt of the robot.